2013
DOI: 10.1515/labmed-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Inter-method comparison of salivary cortisol measurement

Abstract: Background: Salivary cortisol is increasingly used in the diagnostic work-up of suspected Cushing's disease as well as in stress research. In this study, the agreement of different methods for salivary cortisol measurement was assessed. Methods: Saliva samples from five healthy volunteers were distributed to three routine clinical chemistry laboratories. As a reference, all samples were also analyzed using liquid chromatography-tandem mass spectrometry involving stable isotope labeled cortisol for internal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Testosterone EIAs are found to cross-react with other steroids (Chattoraj, 1976) and biological agents (e.g., sex hormone-binding globulin; Pugeat et al, 1981). Consistent with this research Running head: TESTOSTERONE MEASUREMENT IMMUNOASSAYS 4 on testosterone measurement, previous studies of cortisol have revealed differences in predicted salivary cortisol concentrations across assay kits (e.g., Baecher et al, 2013;Miller et al, 2013). These differences have been attributed to differing specifications of kits and cross-reactivity in EIAs.…”
Section: Salivary Hormone Concentrations Are Frequently Measured Withmentioning
confidence: 55%
See 1 more Smart Citation
“…Testosterone EIAs are found to cross-react with other steroids (Chattoraj, 1976) and biological agents (e.g., sex hormone-binding globulin; Pugeat et al, 1981). Consistent with this research Running head: TESTOSTERONE MEASUREMENT IMMUNOASSAYS 4 on testosterone measurement, previous studies of cortisol have revealed differences in predicted salivary cortisol concentrations across assay kits (e.g., Baecher et al, 2013;Miller et al, 2013). These differences have been attributed to differing specifications of kits and cross-reactivity in EIAs.…”
Section: Salivary Hormone Concentrations Are Frequently Measured Withmentioning
confidence: 55%
“…Although many companies manufacture assay kits for commercial use, recent work suggests that these different kits vary in concentration predictions for the same hormones (e.g., Taieb et al, 2003;Baecher et al, 2013;Crewther et al, 2013). Some potential reasons for differences in the estimation of hormone levels across kits include differing levels of sensitivity and specificity across the range of hormonal concentrations, with the lowest and highest concentrations being most prone to quantification errors .…”
Section: Salivary Hormone Concentrations Are Frequently Measured Withmentioning
confidence: 99%
“…It also allows for potential measurement differences between HYENA and DEBATS related to sampling and laboratory analysis: the ELISA (enzyme-linked immunosorbent) method in the DEBATS study and the RIA (radioimmunoassay) method in the HYENA. For morning and evening cortisol levels, the use of the linear relationship between ELISA and RIA methods [35] makes levels of cortisol concentrations directly comparable for the HYDE study. Regression conclusions were similar to those presented in Table 3, carried out without the use of this equation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to controls, RIA gave results much closer to the expected value than ELISA did [33]. Although measurements concerned only 10 samples, Baecher et al (2013) published Passing and Bablock regression of salivary cortisol results reported by immunoassay systems related to a reference (35). Regression equations showed a strong linear relationship between ELISA and RIA methods: RIA = 0.92 (95% CI: 0.87–1.03) × ELISA-0.19 (95% CI: − 0.35 to − 0.04); r = 0.993.…”
Section: Methodsmentioning
confidence: 99%